Anthropogenic shift towards higher risk of flash drought over China - Xing Yuan (Nature Portfolio, 2019)
Flash droughts are widely discussed in the scientific community since the rapid onset of the 2012 drought in the USA. Here, the authors model the temporal frequency of potential flash drought events and the exposure risk over China for the next 80 years.